Diaspora Networks and the International Migration of Skills : How Countries Can Draw on their Talent Abroad - Kuznetsov, Yevgeny (Washington, DC: World Bank, 2012)
Network diasporas are but the latest bridge connecting developing economy insiders, with their risk-mitigating knowledge and connections, to outsiders in command of technical know-how and investment capital. This book examines the interaction of expatriate talent with institutions in expatriates' countries of origin in an attempt to make the potential of diasporas and their knowledge a reality. The question of how to trigger and sustain such a virtuous cycle is a central concern of this book. The focus is on the "how to" details of how to design effective diaspora networks and transform brain drain into brain gain.